EDUCAŢIA MUZICAL-ARTISTICĂ A ELEVILOR: O VEDERE PRAXIOLOGICĂ - USM ADMIN (Moldova State University, 2009)
This article points out the problem of efficiency through the following sizes: from/towards the musical essence. In such a way, we did implications in the essence of the process of artistic influence from/towards. We are going to re-orient the theoretical and methodological thinking of competence factors into efficiency of the didactic process.